2013
DOI: 10.1590/s0085-56262013000100010
|View full text |Cite
|
Sign up to set email alerts
|

Orthoptera assemblages associated with macrophytes of floodplain lakes of the Paraná River

Abstract: ABSTRACT. Orthoptera assemblages associated with macrophytes of floodplain lakes of the Paraná River. The Orthoptera assemblage composition varies considerably, depending on habitat type. This study examines the spatiotemporal relationship between plant diversity, hydrometric level, environmental variables and the Orthoptera richness and abundance in floodplain lakes connected permanently or temporarily with the main channel of the Paraná River. The grasshoppers were collected fortnightly (April 2006-May 2007… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…crassipes submerged and areal parts provide appropriate habitat and trophic resources for insects. At least for Diptera and Odonata assemblages, it was reported that the aquatic plants support assemblages of these insects, abundance and richness of which depend on the abundance and distribution of the vegetation (Capello et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…crassipes submerged and areal parts provide appropriate habitat and trophic resources for insects. At least for Diptera and Odonata assemblages, it was reported that the aquatic plants support assemblages of these insects, abundance and richness of which depend on the abundance and distribution of the vegetation (Capello et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…At each sampling point in native vegetation, a quadrat was placed at random (total N = 90), and photographs were taken and subsequently analyzed to obtain the percentage cover of each host plant using the CorelDRAW X7© program. The analysis of these photographic quadrats is a quantitatively precise means of estimating vegetation cover (Capello et al ., 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Gripp, Personal communication; dos Santos and Esteves, 2002). They do not occur only during the period of new culm growth after a sudden decrease in water level due to sandbar breaching events, indicating great influence by water level fluctuations on their population dynamics (dos Santos and Esteves, 2002;Capello et al, 2013).…”
Section: Introductionmentioning
confidence: 99%